Identification of the Cytotoxic Transglutaminase from Mycobacterium spp. That Is Involved in RIPK1 Activation - Xinting Zhang; Yikai Zhang; Xiao Feng; Yueying Wang; Si-Shang Li; Mei-Yi Yan; Yi-Cheng Sun; Qi Jin; Feng Jiang (Molecules)
Although the global incidence of tuberculosis has declined in recent years, tuberculosis remains a major global public health challenge. The Mycobacterium tuberculosis complex (MTBC) including M. tuberculosis, M. bovis, M. microti, etc., is the deadliest Mycobacterium spp. that needs more attention. Research on M. microti is significant as it is a zoonotic pathogen that can spread between animals and humans. By exploring the function of a transglutaminase in M. microti (MmTG), which is widely distributed in Mycobacterium and other species, a potential cytotoxic effector has been characterized. MmTG inhibits cell proliferation by inducing the phosphorylation of RIPK1 (receptor-interacting serine/threonine-protein kinase 1) and the Cys159 of MmTG is the highly conserved residue related to its cytotoxicity. Understanding MmTG and its homologs can provide more insights into the pathogenic mechanisms of mycobacteria and contribute to the development of more effective therapeutic strategies against mycobacterial infections.